The role of counterfeit consumption on consumers’ psychological needs satisfaction - Rosely, Nurhidayah; Raja Yusof, Raja Nerina; Hashim, Haslinda (Malaysian Consumer and Family Economics Association, 2022)
Consumer demand has been a leading cause for the mushrooming counterfeit markets, and thus these dark markets pose the greatest challenge for luxury brand manufacturers in preventing consumers from participating in counterfeiting activities. This paper, which was based upon a hermeneutic phenomenology study, sought to uncover a rich and contextualised account of 7 consumers’ consumption experiences on the purchase of counterfeit branded fashion goods through in-depth interviews. The phenomenological approach was used to probe into the living experience of consumers involved in counterfeit branded fashion goods consumption, and the consumers were selected via purposive and snowball sampling. The data were analysed using thematic analysis, and six themes emerged from this study; sharing information, trusted sources, social learning, adept, discernment, and deceiving, which unravelled the role of counterfeit consumption in psychological needs satisfaction. This study contributes knowledge to the area of counterfeit branded fashion goods and consumer behaviour as the emerging themes that describe the actual experiences captured from the consumers who were continuously involved in the counterfeit consumption practice. This research contributes to scholarly and managerial knowledge in the Malaysian context through more insights into comprehending the underlying causes of counterfeit consumption phenomena.